MILITARY CORRESPONDENTS AND THEIR CONTRIBUTION TO THE REGIONAL PERIODICAL PRESS OF THE FERGANA VALLEY - Алиназарова Д. В. (TARIXIY TADQIQOTLAR, 2026)
The article examines the periodical press of the Fergana Valley in Uzbekistan on the eve and during the Second World War. The functioning of regional periodicals under wartime conditions is analyzed. The study highlights the activities of military correspondents, photojournalists, freelance authors, as well as linotypists and typesetters of printing houses. Based on archival materials, new names of military journalists who worked at the front and in the rear have been identified.